When There Was No Money Building ACLEDA Bank in Cambodia$1 (Bs Evolving Financial Sector /s - Clark, Heather A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
The largest retail branch bank network is built in one of the most formidable environments in the world. This book takes the journey from Year Zero to the present, tracing the trials and triumphs of a group of people as they built an employment generation project for demobilized soldiers in 1992 into the largest commercial retail bank branch network in Cambodia by 2003. Along the way they influenced the nation$1 (Bs financial system and stimulated a banking industry that serves poor and low-income people. The book offers a tantalizing analysis of events, organizational dynamics and a business model that incorporates profit and purpose. It examines the transition from the microfinance field that is jealously guarded by donors to a breakthrough response of commercial banking for the people.s
Heritage -- Prologue -- Cambodia and the Banking System -- The Accidental Organization -- Discovery -- Prologue -- Exploring the (3z(BMarketspace(3y (B-- Crossroads -- Latitude to Grow -- Velocity -- Prologue -- Confidence: The (3z(BFlywheel(3y (BTurns -- Union -- Odyssey -- Prologue -- To Play by the Rules of the Game -- Inspiration: From the Andes to the Mekong -- Invitation -- Momentum -- The Bank You Can Trust -- Commercial Microfinance and Poverty -- Yesterday, Today and Tomorrow.s
Keywords: Finance; Business; Management science; Development economics; Finance; Finance, general; Business and Management, general; Development Economics; Electronic books